2017
DOI: 10.1111/dme.13312
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and morbidity in offspring of mothers with diabetes compared with a population group: a Danish cohort study with 8–35 years of follow‐up

Abstract: The offspring of mothers with and without diabetes had almost identical mortality. The increased morbidity was restricted to the first 2 years of life, and was primarily attributable to a few individuals with very severe but probably non-diabetes-related disease burden. The large majority of offspring of mothers with diabetes experienced health conditions similar to those not exposed to diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Second, we used paternal diabetes as the negative control exposure to explore potential residential confounding or information bias from genetic factors and shared familial factors such as diabetes-related environment, behaviours and hospital contacts. Third, since diabetes is typically preceded by a period of prediabetes, we evaluated the risk of high RE in mothers have a higher risk of being diagnosed with diabetes in the first 25 years of life [31], we excluded offspring with a diabetes diagnosis to examine the association. Eighth, to take into consideration the influence of ICD code changes since 1994, we restricted a sub-analysis to offspring born after 1994.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Second, we used paternal diabetes as the negative control exposure to explore potential residential confounding or information bias from genetic factors and shared familial factors such as diabetes-related environment, behaviours and hospital contacts. Third, since diabetes is typically preceded by a period of prediabetes, we evaluated the risk of high RE in mothers have a higher risk of being diagnosed with diabetes in the first 25 years of life [31], we excluded offspring with a diabetes diagnosis to examine the association. Eighth, to take into consideration the influence of ICD code changes since 1994, we restricted a sub-analysis to offspring born after 1994.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…We report that among LGA neonates delivered by individuals with diabetes, there is a significantly lower mortality. This finding may be secondary to our large sample size, [43] timing of delivery, [44,45] and close follow-up of offspring with maternal medical conditions. [46][47][48] This article is protected by copyright.…”
Section: Discussionmentioning
confidence: 97%
“…Only 5 children born to women with DIP died during the post-neonatal period resulting in an OR of 3.8 (1.6–9.2). Additionally, two Danish studies have reported on mortality reaching beyond the perinatal period [ 91 , 92 ]. Only the study by Knorr et al in which children born to mothers with type 1 diabetes were followed for one year found an increased mortality during their first year of life, compared to children born to mothers from the background population (Hazard Ratio 2.10, 95% CI 1.33–3.30, p = 0.001) [ 91 ].…”
Section: Longer Term Effects Of Hyperglycemia In Pregnancy On the Off...mentioning
confidence: 99%
“…Only the study by Knorr et al in which children born to mothers with type 1 diabetes were followed for one year found an increased mortality during their first year of life, compared to children born to mothers from the background population (Hazard Ratio 2.10, 95% CI 1.33–3.30, p = 0.001) [ 91 ]. By contrast.another study comprising children of both women with DIP and GDM, found no significant difference in mortality for children born to women with HIP compared to unaffected controls (risk difference 0.09%, 95% CI −0.79–0.98) [ 92 ].…”
Section: Longer Term Effects Of Hyperglycemia In Pregnancy On the Off...mentioning
confidence: 99%